Effects of Media Feminist Approaches on Youth - Minhas, Shahid; Adnan Shahid; Uzman Ali (Journal of Peace, Development and Communication, 2021)
Feminism is tied in with examining sexual orientation contrasts and in regards to supplementing the job of genders in the public eye. Being a feminist it is just having faith in equivalent rights for all sexes. It's not tied in with detesting men. It's not about ladies being superior to men. It's not tied in with shunning womanliness. Pakistani Media is promoting western term of feminism and have recently launched the first feminism based web series CHURAILS. Four women run an office calling themselves CHURAILS. At the point when one of them disappears, their investigation drives them to something a lot greater than themselves. The purpose of this study is to analyze the perceptive of Pakistani youth on feminism, also the effect of feminism on youth, and to explore the digital media content on feminism in Pakistan. An online survey is conducted through social media to which 150 respondents of age 16-30 year old responded. This study highlights that the youngsters of Pakistan are fully aware of the term Feminism and support gender equality. In which the 41% of youth agreed with the concept of gender equality concept of feminism. But the Pakistani Media is portraying the western feminism which is destroying our culture, norms and religious value. This study shows that the wrongly portrayed feminism by Pakistani Media is causing discomfort in gender which will affect the feminist movements in future. This study also shows that web series like CHURAILS is promoting vulgarity among the youngsters.